Stereoselective mechanochemical synthesis of thiomalonate Michael adducts via iminium catalysis by chiral primary amines - Błauciak, Michał; Andrzejczyk, Dominika; Dziuk, Błażej; Kowalczyk, Rafał (Beilstein Journal of Organic Chemistry, 2024)
The study presents a novel approach utilizing iminium salt activation and mild enolization of thioesters, offering an efficient and rapid synthesis of Michael adducts with promising stereoselectivity and marking a significant advancement in mechanocatalysis. The stereoselective addition of bisthiomalonates 1–4 to cyclic enones and 4-chlorobenzylideneacetone proceeds stereoselectively under iminium activation conditions secured by chiral primary amines, in contrast to oxo-esters as observed in dibenzyl malonate addition. Mild enolization of thioesters allows for the generation of Michael adducts with good yields and stereoselectivities. Reactions in a ball mill afford product formation with similar efficacy to solution-phase reactions but with slightly reduced enantioselectivity, yet they yield products in just one hour compared to 24 or even 168 hours in solution-based reactions. It is noteworthy that this represents one of the early reports on the application of iminium catalysis using first-generation chiral amines under mechanochemical conditions, along with the utilization of easily enolizable thioesters as nucleophiles in this transformation.
Keywords: asymmetric catalysis; iminium catalysis; mechanochemistry; organocatalysis; thioesters